Aurora_Australis_V1_2017_Hobart_to_Davis - Martin Walch (2020)
This work was made during the voyage south to undertake the 2017 Australian Antarctic Arts Fellowship at Mawson Station in Antarctica. The project extends earlier research into time-lapse visualisation begun during the ARC funded Derwent Project. It did this through the application of a time-lapse camera, fixed to the perpetually moving platform of an ice-breaker, whilst recording the traverse of the ship across the southern ocean and through the sea ice, from Hobart, Tasmania to Davis Station in East Antarctica.